Exhumation: Past and Present - Levchenko, I.E.; Merenkov, A.V. (KnE Social Sciences, 2021)
The modernization of a society leads to changes in the society’s attitude towards funeral practices. This article is devoted to the study of socio-cultural, historical, religious and political-legal aspects of the exhumation phenomenon. Thanatosociological, historical, biographical, religious studies, legal and political approaches form the methodological basis of the study, which made it possible to identify features of exhumation in the past and present. The study has fixed that modern experts criticize the Russian Orthodox Church (Moscow Patriarchate) for the fact that the return to church life of already known relics and the inclusion of new shrines in it do not always meet the canonical requirements. As a result, gaining and ‘traffic’ of the last decades relics “with their historical unreliability, political background and clerical ambitions” causes direct damage to the spiritual life of a society. It has been established that exhumation, on the one hand, ‘compensates’ for losses in family relationships, gives impetus to the development of religious life, and solves specific problems of scientific research and investigative actions. On the other hand, sometimes exhumation is carried out for opportunistic, political, mercenary or criminal purposes thus, the problem of ensuring the peace of the buried remains very relevant. Keywords: funereal, cemetery, exhumation, reburial, relics